2016
DOI: 10.1038/nm.4223
|View full text |Cite
|
Sign up to set email alerts
|

Influenza immunization elicits antibodies specific for an egg-adapted vaccine strain

Abstract: For broad protection against infection by viruses such as influenza or HIV, vaccines should elicit antibodies that bind conserved viral epitopes, such as the receptor-binding site (RBS). RBS-directed antibodies have been described for both HIV1–3 and influenza virus4–8, and the design of immunogens to elicit them is a goal of vaccine research in both fields. Residues in the RBS of influenza virus hemagglutinin (HA) determine a preference for the avian or human receptor, α -2,3-linked sialic acid and α -2,6-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 36 publications
(42 reference statements)
4
101
0
1
Order By: Relevance
“…Receptor mimicry by CDRH3 is similar to examples we have described previously [1416], although the loop itself is substantially longer. Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Receptor mimicry by CDRH3 is similar to examples we have described previously [1416], although the loop itself is substantially longer. Fig.…”
Section: Resultssupporting
confidence: 80%
“…Residue 226 is Gln in most human H1 isolates, but passage of vaccine strains in chicken eggs can select for a mutation to Arg, because of its preference for the avian receptor [16]. In the vaccine-strain Solomon Islands HA we used for crystallization, residue 226 is indeed Arg, which bridges between HA S136 and T105 at the flexible tip of the antibody CDRH3; Gln could do the same (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain a stable trimeric pre-fusion structure, the C-terminal part of the ectodomain is fused to a trimerization motif, based either on the transcription factor GCN4, as in the case of coronavirus S [70], parainfluenza virus 5 F glycoproteins [71] and Hendra virus F glycoprotein [72], or the T4 fibritin motif, as in the case of respiratory syncytial virus fusion glycoprotein [73]. Even for influenza HA, the dogma of the stability of the trimeric state all along the structural transition could be called into question in view of the growing number of crystalline structures that do not display any threefold symmetry (PDB entry codes: 4EDA, 5A3I 5K9K, 5K9O and 5IBL) [74][75][76][77] (Fig. 4).…”
Section: Differences and Similarities With Other Viral Fusion Glycoprmentioning
confidence: 99%
“…Indeed, as mentioned above, some progresses have already been made for both class I [81][82][83][84]92] and class II fusion glycoproteins [67][68][69]; however, a higher resolution will be required to get a reliable quasi-atomic model of those intermediates. [74] and in two monomeric HA structures [74,77]. Second row: ribbon diagrams of HA2 structure (H3 subtype) [79] as in the prefusion protomer, in two monomeric HA0 structures [76] and as in its trimeric post-fusion conformation [80].…”
Section: Final Remarks and Conclusionmentioning
confidence: 99%
“…Immunologic studies have proposed mechanisms for the lack of antibody cross-reactivity between egg-257 grown and circulating viruses. A study of plasmablasts in individuals receiving influenza 258 A(H1N1)pdm2009 vaccine found that individuals with a highly-specific antibody response to a reversion 259 present in the vaccine strain had no binding to the A(H1N1) circulating strain [22]. With regards to more 260 recent H3N2 strains, similar immunologic patterns of antibody misdirection have been reported for 261 residue 160 in antigenic site B of HA [7].…”
Section: Discussion 234mentioning
confidence: 71%